Scientific Status of Philosophical Anthropology - Soghomonyan, Gagik (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
Man’s choice always has an eschatological perspective, the course of human history and its completion depends on which path he takes: life or death - Civilization is gradually approaching a tempting but extremely dangerous limit, beyond which the influence of uncontrollable forces can be fatal for a person. It’s time to sober up. In this regard, the role and importance of philosophical anthropology is undeniable. Two directions are distinguished in philosophical anthropology: philosophical anthropological essentialism and existentialism. Essentialist philosophical anthropology examines man’s relationship with nature, society, and culture, and existentialist philosophical anthropology examines man’s relationship with God, others, and himself. The subject, problems and scientific status of philosophical anthropology are presented. The idea is that it is too early to forget and abandon the substantiated rich research toolkit of philosophical anthropology. As a result of analysis, the author comes to the conclusion that a person has some positive qualities, developing and relying on those it is possible to improve the social environment and interpersonal relationships. For this, it is necessary to develop the knowledge about the person himself, taking into account the anthropological aspects of the economic, social and institutional reforms being implemented.